Psychoemotional and cognitive characteristics in patients at the early stages of Parkinson’s disease - A. V. Demchenko; V. V. Biriuk (Zaporožskij Medicinskij Žurnal)
The purpose of the study was to assess psychoemotional and cognitive characteristics in patients at the early stages of Parkinson’s disease (PD) by neuropsychological and neurophysiological examinations.